1978
DOI: 10.1042/bj1750091
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in horse ferritins. A comparative study of surface charge, iron content and kinetics of iron uptake

Abstract: Horse ferritins from different organs show heterogeneity on electrofocusing in Ampholine gradients. Both ferritin and apoferritin from liver and spleen could be fractionated with respect to surface charge by serial precipitation with (NHI4)2SO4. In the ferritin fractions, increasing iron content parallels increasing isoelectric point. After removal of their iron those fractions which originally contained most iron accumulated added iron at the fastest rates. When unfractionated ferritins from different organs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…Evidence linking subunit heterogeneity of HoSF with iron content has been reported previously, although prior to a full understanding of the subunit composition of HoSF [76]. This earlier study reported that the iron content of bands observed in isoelectric focusing correlated with the surface charge of the protein in the bands.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Evidence linking subunit heterogeneity of HoSF with iron content has been reported previously, although prior to a full understanding of the subunit composition of HoSF [76]. This earlier study reported that the iron content of bands observed in isoelectric focusing correlated with the surface charge of the protein in the bands.…”
Section: Discussionmentioning
confidence: 59%
“…These results are in agreement with sedimentation results described here. It is interesting to note that the number of bands (~11) observed using isoelectric focusing of various samples [76] corresponds favorably with the number of species calculated from the binomial function (Fig. 11A).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, chronic immunization with the highly anionic unmodified apoferritin (46) results in the formation of circulating immune complexes that subsequently deposit in glomeruli, as we have shown in this and previous studies using this model (18,47). In either circumstance, complement depletion or its absence leads to decreased glomerular clearance of immune complexes (34,44,(47)(48)(49), highlighting the relevance and complexities of the complement system in immune complex processing in the glomerulus (3,45).…”
Section: Discussionmentioning
confidence: 65%
“…Ferritin is present not only in cells but also in sera, and the serum ferritin level is positively correlated with body iron stores [1-3, 12, 15, 18]. The major function of tissue ferritin is to detoxify and store intracellular iron [8], and it contains a large amount of iron [5,14,17]. Serum ferritin has been found to have different amounts of iron in some mammals [6,9,13,20,22].…”
mentioning
confidence: 99%